Uma contribuição aos estudos sobre a relação transporte e crescimento urbano: o caso de João Pessoa - Oliveira, José Luciano Agra de (2006)
The necessary understanding of the nature of the relation between transportation and urban development demands a good knowledge of the origin process and evolution of the cities, the elements that contribute for the definition of its structure and forms and quality of urban life. The work presents a bibliographical revision on some historical aspects of the origin and evolution of the cities, the main events of its development, the paper that the forms of mobility in the past had had in the space configuration and the importance of the system of transportation in the consolidation of these cities. The developed research searched to rescue a little of the history of the evolution of the city of João Pessoa and to investigate the role played for the system of transportation as part of this process. The evolution of the city of João Pessoa of its origin until nineteen century was presented from the perception that if had at the time of the city. The evolution of the Paraiba´s capital in twenty century until the 60´s deeply was marked by the impulse in the increase of the population, the commercial activities and for the interventions of the government. This interventionist politics consolidated of definitive form in one same urban structure the Center and the quarters of the east and south zones of the city. The decade of seventy represented a definitive landmark in the space organization and the system of transportation of the city. The city of João Pessoa passed to be planned of integrated form, associating development and transport, in less filing way and with bigger severity technician. In the work the proposals of the main plans of development of use of the ground and transportation of the city are presented. The city of João Pessoa duplicated of size between 1972 and 1983 presented the effect of intense process of urbanization, from there studies are elaborated and the managing plan of transportation that go to define in a horizon of 20 years the system that functions in the city. The work rescued information to directly understand the public intervention in the operation of transports, presents plans of mass transport, it analyzes the proposal of transportation of the Managing Plan of the City and if it keeps in general in the examination of the first operational data set of the functioning of the city’s buses and the transports in the metropolitan area. Finally, it presents the profile of the urban evolution analyzing aspects of the form and extension of the land use, the dynamics of the vectors of city’s growth, the densities and the production of the urban space. It also analyzes the evolution of the transports and its main pointers as itinerary, ways and the behavior of the movement of passengers of the urban buses of the Paraiba´s capital.